Association of long lasting unsurmountable histamine H2 blockade and gastric carcinoid tumours in the rat. Issue 12 (December 1985) - Poynter, D; Pick, C R; Harcourt, R A; Selway, S A; Ainge, G; Harman, I W; Spurling, N W; Fluck, P A; Cook, J L
Abstract : The oral administration of loxtidine, a potent histamine H2-antagonist, to a total of 378 rats at doses of 50, 185, or 685 mg/kg/day for 116 weeks resulted in the late formation of carcinoid tumours of the gastric fundus. The first such tumour was detected after 712 days of treatment. There was no dose related response; 11 rats at the low level of treatment were affected, 12 at the intermediate and 11 at the high. Twenty seven females but only seven males were affected. No gastric tumours were found in the 228 controls. There is no evidence that loxtidine acts as a direct carcinogen and it is suggested that the tumours were the result of prolonged achlorhydria produced by a potent unsurmountable histamine H2 receptor antagonist.